2020
DOI: 10.1177/1049732320912410
|View full text |Cite
|
Sign up to set email alerts
|

Falling Down the Rabbit Hole: Child and Family Experiences of Pediatric Hematopoietic Stem Cell Transplant

Abstract: Pediatric hematopoietic stem cell transplant (HSCT) is an intensive treatment that can be life-threatening. All family members experience distress. We conducted a grounded theory study using a family systems-expressive arts framework to develop a theoretical understanding of the family experience of HSCT. Six families (15 family members) participated in two interviews, drew an image, and were guided through a “dialoguing with images” process. Participants did not always perceive HSCT as an experience they had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 46 publications
2
26
0
1
Order By: Relevance
“…Time periods leading up to HSCT hospital admission, while hospitalized awaiting neutrophil engraftment, and at HSCT hospital discharge were especially difficult. This is consistent with prior work identifying that parents encounter critical time periods at hospital admission, during inpatient monitoring, and again at discharge when parents encounter general overwhelm acclimating to the healthcare setting and HSCT caregiving activities (Kaziunas et al, 2016;Liu et al, 2020a;West et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Time periods leading up to HSCT hospital admission, while hospitalized awaiting neutrophil engraftment, and at HSCT hospital discharge were especially difficult. This is consistent with prior work identifying that parents encounter critical time periods at hospital admission, during inpatient monitoring, and again at discharge when parents encounter general overwhelm acclimating to the healthcare setting and HSCT caregiving activities (Kaziunas et al, 2016;Liu et al, 2020a;West et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…These interactions play a critical role in the ways parents respond to HSCT stressors, develop confidence in caring for their children, and assign positive meaning to HSCT. For example, West et al (2020) found that parental suffering was not routinely recognized during hospitalization. However, when clinicians offered emotional support and human social interaction, these relationships had a lasting and meaningful impact on the parent (West et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Desde o final do século XX, cada vez mais estudos tem demonstrado o uso de tecnologias educacionais para o cuidado da vida e saúde de pessoas, grupos e comunidades, pois a tecnologia apresenta potencial poder de educar e trazer a consciência do empoderamento do cuidar [15][16][17] .…”
Section: Discussionunclassified